A Collision Arbitration Protocol Based on Specific Selection Function. Issue 4 (1st July 2017) - Su, Jian; Ren, Yuqing; Yang, Ying; Han, Yu; Wen, Guangjun
Abstract : Fast and effective identifications of a large number of items are required in many Radio‐frequency identification (RFID) applications. Simultaneous responses from multiple tags are corrupted by collisions and thus result in low identification efficiency. To address the problem of low identification efficiency, many existing tag anticollision algorithms try to schedule the identification process to avoid collisions. A novel anti‐collision scheme based on specific selection function is presented, in which tags pick a slot according to a selection function instead of being randomly assigned to slots within a frame. If collision occurs, the reader sends the custom command SETBM according to the collision information. When probed by the SETBM, the tags apply the selection function to its partial ID and send the mapped result to the reader. According to the mapped result, the reader assigns the time slot to the tags. All tags collided in the same slot will be identified by the tree traversal scheme. Compared to the most of existing anti‐collision algorithms, simulation results show that our proposed algorithm can achieve better performance in terms of identification efficiency, time efficiency, and energy consumption.